Hubungan Pengetahuan Ibu tentang Anemia, Pola Makan, dan Kepatuhan Konsumsi Tablet Fe terhadap Kejadian Anemia pada Ibu Hamil di Klinik PT Rea Kaltim Pantations Tahun 2022 - Khotimah, Khusnul (MPI Press, 2023)
Introduction: Anemia in pregnant women is a condition of reduced red blood cells (erythrocytes) in the blood circulation, where rate Hb pregnant women, 9% of pregnant women worldwide. The condition of anemia can hurt pregnant women and the fetuses they contain. Objectives: This study aims to determine the relationship between the knowledge of pregnant women about anemia, diet, and adherence to the consumption of Fe tablets to the incidence of anemia in pregnant women at the PT REA Kaltim Plantations Clinic in 2022. Method: This study used a descriptive-analytic research design, using a quantitative method approach cross-sectional. The number of samples in this study was 30 respondents using a total sampling technique because the population did not reach 100, so the entire population was used as the research sample. The research instrument used in this research was the Guttman scale questionnaire—bivariate analysis using Chi-Square. Result: The results of the study showed that the relationship between the level of maternal knowledge and the incidence of anemia was obtained by P-value = 0.004, (OR = 10.500), the relationship between diet and the incidence of anemia was obtained by P-value = 0.001 value (OR = 17.500), the relationship between adherence to consuming Fe tablets and The incidence of anemia obtained a P-value = 0.001 (OR = 28.600). Conclusion: There is a significant relationship between maternal knowledge, dietary patterns and compliance with the consumption of blood-boosting tablets and the incidence of anemia in pregnant women at the PT REA Kaltim Responses Clinic in 2022.